Compact-Size Wideband Circularly-Polarized Dipole Array Loaded Metasurface for RFID readers - Huỳnh Nguyễn Bảo Phương; Đặng Thị Từ Mỹ (My University, 2024)
Compact-Size Wideband Circularly-Polarized Dipole Array Loaded Metasurface for RFID readers
Keywords: RFID reader; Metasurface; Dipole array